Advanced engineering mathematics - Kreyszig, Erwin (New York : John Wiley & Son, Inc., 2011)
Advanced Engineering Mathematics, 10th Edition is known for its comprehensive coverage, careful and correct mathematics, outstanding exercises, and self-contained subject matter parts for maximum flexibility. The new edition continues with the tradition of providing instructors and students with a comprehensive and up-to-date resource for teaching and learning engineering mathematics, that is, applied mathematics for engineers and physicists, mathematicians and computer scientists, as well as members of other disciplines.